EVOLUTION OF THE RUSSIAN CONCEPT OF STRATEGIC DETERRENCE - Radivojević Kovačević, Natalija; Hatidža, Beriša; Zgonjanin, Srđan (National interest, 2026)
This article explores the evolution of Russia’s strategic deterrence concept from the Cold War era to the current conflict in Ukraine. The primary goal is to analyze how Russia’s nuclear and military doctrines have transformed and how deterrence has become a multidimensional instrument of national security. By applying content and comparative analysis methods, the paper contrasts the Russian approach with the Western (primarily American) paradigm. The findings reveal that Russia’s deterrence model has expanded significantly, incorporating not only nuclear and conventional capabilities, but also cyber, economic, and ideological tools. The study concludes that deterrence in the Russian context surpasses traditional defensive purposes and becomes an active element of power projection in a complex global security environment.
Keywords: strategic deterrence; nuclear weapons; Russian military doctrine; Russian Federation; contemporary conflict; United States; geopolitics